Polymicrogyria Clinical/Imaging Heterogeneity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at the Royal Children's Hospital. Melbourne, Australia, and other international centers studied the imaging features of 328 patients with polymicrogyria referred from 6 centers, with detailed clinical data for 183 patients.